The business benefits of cyber security for SMEs. Issue 2 (February 2020) - Lloyd, Guy
Abstract : Cyber security is often discussed in terms of data breaches, regulatory fines and business disruption. The advantages are seldom highlighted. For example, effective cyber security makes it possible for companies to innovate and this drives revenue, profit and growth. Defending against cybercrime can deliver genuine benefits for small and medium-size enterprises (SMEs) and result in more valuable organisations. Cyber security is often discussed in terms of data breaches, regulatory fines and business disruption. However, the advantages are seldom highlighted. Effective cyber security makes it possible for companies to innovate and this drives revenue, profit and growth. Defending against cybercrime can deliver genuine benefits for small and medium-size enterprises. And as organisations of all sizes move towards driving efficiency through digitising processes, it's important for business leaders to redefine how they think about security, argues Guy Lloyd of CySure.